Automatic Question Paper Generation using ML: A Review - et. al., Kanchan Babaji Dhomse, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
In any instructive field educational programs, the courses are characterized with learning goals. It is exceptionally challenging for the instructors to create Question Papers with changed questions. There's no standardizing strategy to guarantee quality of question paper. Consequently, there arises a have to be have a framework which can consequently produce it from we entered information inside few seconds. It’s basic to specify tests and exams, it plans understudies in their journey for information, so having a legitimate examination paper & organize is essential. Now the traditional strategy of producing address paper has been manual and it is exceptionally time and cost expending to diminish these things we developed this framework which is able make the programmed address paper and this it can be valuable to numerous instructive establishing.